Chaplaincy and spiritual care in mental health settings - Fletcher, Jean (London ; Philadelphia : Jessica Kingsley Publishers, 2019)
"This edited collection about good practice for mental health chaplains and other related professionals looks at how spirituality is viewed across mental health fields. It identifies what mental health chaplaincy is, how mental health chaplaincy interacts with other organisations like the NHS, and what good practice means with examples of positive and fulfilling experiences in mental health settings. The chapters consider some of the main issues of working with the mental health community, such as the place of volunteers, the recovery process, religious diversity and patient safety. They are followed by uplifting case studies, including service user perspectives, to provide a valuable overall insight into mental health chaplaincy and its context in wider mental health services"--
What is a mental health chaplain for? / Simon Harrison -- The clinician's view of spirituality in mental health care / Chris Cook and Lucy Grimwade -- Seeking an authentic Christian voice on mental health / Ben Ryan -- Bridging the gap: the interface between NHS care and faith communities / Neil Bunker -- Has professionalism gone too far? The place of volunteers in mental health chaplaincy / Richard Allen -- Entering by another door... / Cameron Langlands -- Religion and spirituality in chaplaincy in mental health care / Ruth Bierbaum -- Responsive, inclusive, diverse / Emma Louis and Feroza Isakjee -- Exploring spirituality in recovery: models of partnership / Charlotte Collins, Rianna Jeffrey and Sarah Boyle -- Spiritual care in the presence of dementia / Peter Kevern and Dawn Brooker -- A companioning presence in the city, chaplaincy in Seattle USA / Kae Eaton -- A Muslim perspective on living well with good mental health / Monawar Hussain -- Through a glass darkly: the world of forensic mental health care / Sally Horner -- Creating liturgies of sanctuary in a mental health inpatient setting / Rachel Allen -- Psychosis and spirituality / Jeremy Law -- Deep talk: finding the story in our life / Judith Gilbert -- Resilience in mental health in living with a learning disability: Cathol Sutherland of L'Arche, Inverness / Jim Cargin -- 'The visiting moon', a memorable pastoral encounter in a mental health setting / Jean Fletcher.
Includes bibliographic references.
Keywords: Mental health clergy; Church work with the mentally ill; Psychology, Religious